737 Supporting Surgeons in Their Return to Training. (12th October 2021) - Richardson, R; Siddiqui, S; Little, Z; Pollard, R; Chan, S
Abstract: Aim: t any one time, approximately 10% of the junior doctor workforce (∼5000 doctors) take time out of training. Following the Bawa Gaba case, and with trainees shielding during the COVID pandemic, there is greater scrutiny and demand to support trainees returning to the frontline. Supported Return to Training (SuppoRTT) is a Health Education England Program designed to improve the Return-To-Training (RTT) experience. For surgical specialties there are additional challenges of reintroducing trainees to practical skills. Method: e designed and facilitated the first regional SuppoRTT course for Orthopaedic Specialist Registrars, which consisted of peer and consultant-led clinical updates, forum discussions and externally commissioned professional coaching. A pre-course survey established participants' concerns and expectations about RTT and formed the basis of discussions. A post-course survey assessed value of the course and impact on participants. Results: Eight participants (6 female) attended. Grade of training on return ranged from ST3 to ST8. Main areas of concern related to colleague perception, reduced confidence with decision-making, operative skill fade, and frustrations with organisational elements of managing work-life balance. There was an overwhelmingly positive response to the support offered on our course, particularly to the discussions around RTT concerns and returning to on-calls. All respondents strongly agreed that sharing their concerns and hearing about peer experience was valuable. Conclusions: High numbers of trainees take approved time out of training. RTT is associated with anxiety around performance and safety. Surgical trainees can be supported with a targeted course that offers clinical update, peer support and professional coaching.